Предмет: Алгебра,
автор: evamartinuk198
Спростіть вираз 5(3 x - 2 у ) – 3(5 x – 3 у ).
Ответы
Автор ответа:
0
Ответ:
Объяснение:
5(3 x - 2 у ) - 3(5 x - 3 у ) = 15х - 10у - 15х + 9у = -у
Автор ответа:
0
Ответ:
-у
Объяснение:
5(3х - 2у) - 3(5х - 3у) =
15х - 10у - 15х + 9у = (15х - 15х) + (-10у + 9у) =
0 + (-у) = 0 - у = -у
Похожие вопросы
Предмет: Химия,
автор: annafedekovuch
Предмет: Информатика,
автор: Natashka335
Предмет: Физика,
автор: sosiso4ka195
Предмет: Русский язык,
автор: NEEKETE
Предмет: География,
автор: KirillSolidov